Identifikasi Body Composition (Healthy Fitness Zone) dan Resiko Cedera pada Pemain Bola Basket SMA - Arfin Deri Listiandi; Didik Rilastiyo Budi; Rohman Hidayat; Ayu Rizky Febriani; Ajeng Dian Purnamasari; Fuad Noor Heza; Rafdlal Saeful Bakhri (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
This study aims to identify Body Composition consisting of Body Mass Index and Body Fat Percentage using the Healthy Fitness Zone norm of the fitnessgram with the risk of injury to high school basketball players. This study uses a descriptive correlationalresearch method, the research sample is students of SMAN 4 and SMAN 5 Purwokerto who follow extracurricular selected using purposive sampling a number of 20 boys and 10 girls. The research instruments used were body composition measurements using Bioelectrical Impedance Analysis (BIA) and Functional Movement Screening (FMS) tests for risk of injury. The results showed that the measurement of the Body Mass Index of students who took basketball extracurricular activities was in the Healthy Fitness Zone criteria of 77%. The percentage of body fat of students who take basketball extracurricular activities is mostly within the criteria of Healthy Fitness Zone 23 students (77%) and multiple correlation value (R) = 0.674 and sig. = 0.000 < 0.05 then the relationship is significant, or it can be stated that there is a significant relationship between Body Mass Index and Body Fat Percentage with Functional Movement Screening. The results of the regression test show that the value of R square = 0.454, the magnitude ofthe relationship between Body Mass Index and Body Fat Percentage with Functional Movement Screening is 45.4% while the remaining 64.6% is influenced by other factors.